The usefulness of the basophil activation test in monitoring specific immunotherapy with house dust mite allergens - Czarnobilska, Ewa M.; Bulanda, Małgorzata; Śpiewak, Radosław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : In clinical practice, reliable tools for monitoring specific immunotherapy (SIT) are of utmost importance. Aim : To assess the usefulness of the basophil activation test (BAT) in monitoring SIT in paediatric patients with allergy to house dust mites (HDM). Material and methods : Thirty-one children qualified for SIT with HDM, of whom 21 completed the SIT during the observation period. The BAT was carried out prior to commencing the SIT (time point BAT1) and upon finishing the initial pack of allergy vaccine (cumulative dose of allergen 12487.5 PNU; BAT2), as well as after the second vaccine pack (cumulative dose of allergen 23750.0 PNU; BAT3). Peripheral blood of the patients was stimulated with allergen solutions in five concentrations from 0.00225 ng/ml to 22.5 ng/ml. Basophil activation was measured by CD63 expression in flow cytometry. Results : For the allergen concentration of 0.225 ng/ml, a statistically significant decrease in median basophil activation was observed, from 51.29% at BAT1 to 8.48% at BAT2 (p = 0.004) and 4.21% at BAT3 (p < 0.001). For the allergen concentration of 0.0225 ng/ml, a statistically significant decrease was seen between BAT1 (1.72%) and BAT3 (0.21%, p = 0.01). Median CD-sens index decreased significantly from 1099.02 at BAT1 to 179.31 at BAT2 (p < 0.002) and 168.04 at BAT3 (p < 0.001). Conclusions : There is a significant decrease in BAT results in the course of specific immunotherapy with HDM allergens in children, with the optimum allergen concentration for monitoring basophil response at 0.225 ng/ml. The CD-sens index seems to be a better monitoring parameter than the plain percentage of CD63-expressing basophils.